Person-centred therapy with children and young people - Smyth, David (Psychotherapist) (Los Angeles : SAGE, 2013)
This book combines traditional person-centred theory with child development concepts to provide a new'child-centred' model for counsellors and psychotherapists. Practical and pedagogical, Smyth writes with a unique warmth of style and personal approach.
Includes bibliographical references (p. [201]-212) and index.
Keywords: Child; Adolescent